(untitled) (Papeles, 2018)
Football fans were transformed in the course of the twentieth century. A new role led them to actively participate in the game from the stands and “continue the game” on the streets. In this way, the purpose of the article is to build a bibliographic review of the studies published by Colombian researchers, whose benchmark of analysis is the supporters or the “barras bravas”. The databases of CLACSO, Dialnet, FLACSO, RedALyC and SciELO were consulted with the purpose of tracking bibliographic references. In this way, the bibliography published from 2001 to 2018 was selected. One of the results shows that the categories of rituals, violence, identity, endurance, school, public policies and symbols are used more regularly to understand and explain the expressions and behaviors of supporters or “barras bravas”. Finally, the fans, in the “barras bravas”, build ways of relating from common experiences, constituents of similarities and differences in the context of football.